2003
DOI: 10.1523/jneurosci.23-04-01169.2003
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Hyperpolarization-Activated Pacemaker Channels Drive Neuropathic Pain

Abstract: Neuropathic pain is a common and often incapacitating clinical problem for which little useful therapy is presently available. Painful peripheral neuropathies can have many etiologies, among which are trauma, viral infections, exposure to radiation or chemotherapy, and metabolic or autoimmune diseases. Sufferers generally experience both pain at rest and exaggerated, painful sensitivity to light touch. Spontaneous firing of injured nerves is believed to play a critical role in the induction and maintenance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
317
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(354 citation statements)
references
References 66 publications
31
317
6
Order By: Relevance
“…The influence of I h on overall cellular excitability is dependent on at least two major factors, channel isoform and subcellular distribution (Chaplan et al, 2003;Strauss et al, 2004;Fan et al, 2005). This study focused on identifying the major HCN channel isoform underlying the generation of I h and regulation of excitability in mouse RTN neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of I h on overall cellular excitability is dependent on at least two major factors, channel isoform and subcellular distribution (Chaplan et al, 2003;Strauss et al, 2004;Fan et al, 2005). This study focused on identifying the major HCN channel isoform underlying the generation of I h and regulation of excitability in mouse RTN neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These can be at multiple sites along the axons, including distal terminals. Evidence from earlier studies has implicated multiple sites in the generation of ectopic activity, including peripheral nerve terminals (Albrecht et al, 2006;Kauppila et al, 2002;Pare et al, 2007), at the site of nerve injury (Bird et al, 2007;Coward et al, 2000;Devor et al, 1993;Novakovic et al, 1998;Omana-Zapata et al, 1997a,b;Tal and Eliav, 1996), along the nerve (Amir et al, 2005;Gold et al, 2003;Pertin et al, 2005), adjacent nerves (Sotgiu et al, 2006), and in the dorsal root ganglia (Amir et al, 1999;Chaplan et al, 2003;Craner et al, 2002;Liu et al, 2000bLiu et al, , 2002Michaelis et al, 2000;Na et al, 2000;Novakovic et al, 1998;Omana-Zapata et al, 1997a,b;Study and Kral, 1996;Xie et al, 1995).…”
Section: Site Of Generation Of Peripheral Drivementioning
confidence: 99%
“…So far, only three groups succeeded in expressing HCN3 in heterologous systems. [21][22][23] Moreover, unlike for HCN1, HCN2, and HCN4, a murine knockout model is not yet available for this channel. We became interested in HCN3 because our previous work indicated that this channel is present in murine ventricle, suggesting that it may also be relevant for cardiac function.…”
mentioning
confidence: 99%